The use of prevention through design as a management tool: a systematic review (Research, Society and Development, 2022)
The Prevention Through Design – PtD can be used as a project management and coordination tool, which aims to reduce the number of accidents in civil construction. Therefore, it is necessary to understand the occupational health and safety scenario to establish preventive control measures. In this sense, it is important that prevention is effective, whether in the concept design or execution phase. Thus, this study aims to investigate works that have addressed the PtD, seeking to analyze its usability as a management tool, also pointing out its positive and negative aspects. The methodology followed the guidelines of the Preferred Report Items for Systematic Reviews and Meta-Analysis (PRISMA), using keywords in agreement with the Boolean descriptor “AND” such as: “prevention through design”, “management”, “construction”, “occupational safety”, “design” and “design for safety”. Initially, 624 articles were found, but with the application of filters, 30 articles remained for full reading. After the complete reading, 14 articles were included for detailed analysis. It was observed that in underdeveloped countries, the tool is not applied. However, in more developed countries the Prevention Through Design – PtD tool is highly requested for accident prevention. Finally, it is understood that there is a cost linked to the accident management tool, however it is seen that when it is implemented, the number of accidents is reduced, which makes the tool effective.